Particulate matter 2.5 promotes HIF-1α-associated autophagy and epithelial–mesenchymal transition in 3D retinal pigment epithelial spheroids - Da Hye Kim; EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Hyesook Lee; Su Hyun Hong; Gi Young Kim; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2026)

Nrf2-dependent redox regulation protects myoblasts from polystyrene nanoplastic-induced premature senescence - Chae Rin Jung; EunJin Bang; Gi-Young Kim; JaeHun Cheong; Yung Hyun Choi (Genes & Genomics, 2026)

Particulate matter 2.5 stimulates pyroptosis and necroptosis via the p38 MAPK/Akt/NF-κB signaling pathway in human corneal epithelial cells - Da Hye Kim; Hyesook Lee; Min Yeong Kim; Hyun Hwangbo; Seon Yeong Ji; EunJin Bang; Su Hyun Hong; Gi Young Kim; Sun-Hee Leem; Dongryeol Ryu; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2025)

Urban aerosol particulate matter promotes mitochondrial oxidative stress-induced cellular senescence in human retinal pigment epithelial ARPE-19 cells - EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Da Hye Kim; Jung-Hyun Shim; Sung-Kwon Moon; Gi-Young Kim; Jaehun Cheong; Yung Hyun Choi (Environmental Toxicology and Pharmacology, 2023)

The Analyses of Cetacean Virus-Responsive Genes Reveal Evolutionary Marks in Mucosal Immunity-Associated Genes - Oksung Chung; Ye-Eun Jung; Kyeong Won Lee; Young Jun An; Jungeun Kim; Yoo-Rim Roh; Jong Bhak; Kiejung Park; Jessica A. Weber; Jaehun Cheong; Sun-Shin Cha; Jung-Hyun Lee; et al. (Biochemical Genetics, 2022)
Viruses are the most common and abundant organisms in the marine environment. To better understand how cetaceans have adapted to this virus-rich environment, we compared cetacean virus-responsive genes to those from terrestrial mammals. We identified virus-responsive gene sequences in seven species of cetaceans, which we compared with orthologous sequences in seven terrestrial mammals. As a result of evolution analysis using the branch model and the branch-site model, 21 genes were selected using at least one model. IFN-ε, an antiviral cytokine expressed at mucous membranes, and its receptor IFNAR1 contain cetacean-specific amino acid substitutions that might change the interaction between the two proteins and lead to regulation of the immune system against viruses. Cetacean-specific amino acid substitutions in IL-6, IL-27, and the signal transducer and activator of transcription (STAT)1 are also predicted to alter the mucosal immune response of cetaceans. Since mucosal membranes are the first line of defense against the external environment and are involved in immune tolerance, our analysis of cetacean virus-responsive genes suggests that genes with cetacean-specific mutations in mucosal immunity-related genes play an important role in the protection and/or regulation of immune responses against viruses.

Identification of Softness Syndrome-Associated Candidate Genes and DNA Sequence Variation in the Sea Squirt, Halocynthia roretzi - Hyun Kook Cho; Bo-Hye Nam; Hee Jeong Kong; Hyon Sob Han; Young Baek Hur; Tae Jin Choi; Yung Hyun Choi; Woo Jin Kim; JaeHun Cheong (Marine Biotechnology, 2008)